Rapid Entire Body Assessment for Work Posture’s Analysis of A Pig Farmer in Bali: A Preliminary Study - Sugiantini, Ni Made Hari; Prapti, Ni Ketut Guru; Raya, Nyoman Agus Jagat; Saputra, I Kadek (Journal of A Sustainable Global South, 2023)
Traditional pig farmers have a high potential and intensity of exposure to ergonomic hazards. Rapid Entire Body Assessment (REBA) is one of the universal instruments relied upon to assess the ergonomic hazards of work postures. This study aimed to analyze the work postures of traditional pig farmer in Bali. This research is a preliminary study with an observational approach. One pig farmer was involved in this study. REBA was used to analyze the subject's work posture, including finding the risk category of the work posture performed. The subject data were analyzed to obtain each group's score consisting of a score of 6 for group A analysis, 5 in group B, 8 in group C, and 2 additional scores. The results showed that the pig farmer had a high-risk work posture, with a work posture’s score of 10. Reba in this study has the potential to comprehensively analyze the subject's posture. Further investigation of work posture among traditional pig farmers are recommended using REBA.